(untitled) (Baghdad Science Journal, 2023)
The aim of the research is to study the biology, life cycles, distribution and structure of the reproductive organ of Leucozonella retteri in natural conditions. Zoological and malacological methods are used in the work. The collection of the material was carried out according to A.A. Shileiko method. According to the results of the conducted studies, the differences between Leucozonella retteri and other species in the structure of the reproductive organ were manifested in the following. The lower part of the sperm is straight, the ovary is slightly curved. The paw pad is 8, located in 4x2 positions. The stylophore is large spherical. The vagina is cylindrical, its length is 5-6 times greater than the width. The penis is large and convex. In natural conditions, egg laying of mollusks is observed at an average air temperature of 17-19° C, air humidity of 70-80%. In Leucozonella Retter, population variability was more pronounced than biotopic variability. The biology and distribution of the Leucozonella retteri species in the natural conditions of the territory of Uzbekistan was studied for the first time. It was found that the species Leucozonella retteri has a significant variability in quantitative indicators, i.e. morphometric sizes, compared with the qualitative variability of morphological signs of blood The results of the research showed that in arid climate, the variability of all the signs of the shell is manifested depending on the habitat.